Analysis Of Behavior And Chemical Stabilization Of Highly Plastic Local Excavated Soil for Embankments In The IKN Highway Project Segment 3A From Karangjoang To KKT Kariangau - Yanuar, Mohammad Iqbal; Wahyudi, Herman; Lastiasih, Yudhi; Prayitno, Dedi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The development of IKN Nusantara (Indonesia's New Capital City) in phase I, 2022-2024, focuses on basic infrastructure development, one of which is the IKN Toll Road Segment 3A Karangjoang - KKT Kariangau (STA 14+000 - STA 25+909) in Balikpapan. This development will add back to Indonesia's infrastructure assets, especially the Ministry of Public Works and Public Housing. One of the main works in the construction of this toll road is excavation and embankment work, the need for a lot of embankment material is a problem in itself so that the excavated soil as much as possible is sought to be used as embankment soil by mixing the excavated soil with fly ash and bottom ash from Balikpapan Steam Power Plant, this is one form of soil stabilization experiment. The mixture testing was carried out by making 3 types of mixture variations namely soil + fly ash, soil + bottom ash, and soil + fly ash & bottom ash, the 3 types of mixtures were tested by standard proctor test and then continued with soaked CBR testing with 0, 7 and 14 days of curing. From these mixes, the highest soaked CBR test result value was 6.013% from the soil + BA 15% mix with 0 days of curing and the lowest value was 0.709% from the soil + FABA 10% mix with 14 days of curing. Due to the negative trend of the soaked CBR test results where the average value is below 6%, the mixed material is not recommended for use.